(untitled) (Global Journal of Management and Business Research, 2025)
In the context of unprecedented geopolitical economic and supply chain disruptions in Eastern Europe over the past decade the role of financial controlling in retail has undergone a fundamental transformation This article offers a comprehensive practitioner-driven analysis of adaptive financial controlling in the high-volatility environment of the Ukrainian and broader Central and Eastern European CEE retail sector Drawing from my experience as a Key Account Manager in leading multinational and local retail companies- including managing through the collapse of major clients currency devaluations and war- I present a novel adaptive controlling cycle specifically tailored for markets exposed to extreme uncertainty The research employs a mixed-methods approach integrating operational data from the Ukrainian home appliance market 2018 2025 benchmarking against Poland and Lithuania and qualitative insights from industry peers and published reports GfK Euromonitor PwC